Peningkatan Potensi Kampung untuk Kesejahteraan Ekonomi dan Gizi Keluarga Kelurahan Katimbang - Mulat, Trimaya Cahya; Saragih, Hondor; Asmi, Syamsinar; Sofiana, Sofiana; Rahmat, Rezqiqah Aulia (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
A strong rural economy refers to the success and sustainable economic growth of rural areas. This involves developing local economic sectors such as agriculture, fisheries, creative industries, tourism, and others. In a strong village economy, villagers have better access to resources, markets, job opportunities, and social services that can improve their well-being. This PkM aims to improve crop processing skills, develop local marketing access, and increase family nutrition awareness. Problem solving methods involve education, training, and consultation. This program is expected to make a positive contribution by increasing the added value of harvests, creating economic opportunities and improving the nutritional conditions of families. The structured approach includes observation, interviews, training and thorough evaluation. With a community service approach, it is hoped that this program will provide real and sustainable solutions to the problems of economic welfare and nutritional conditions of families in Katimbang Subdistrict which can be achieved through this collaborative and structured effort.